Factors Effecting the Electrophoretic Mobility of Prothrombin - Peacock, Andrew C.; Reed, Roswell A. (Thrombosis and Haemostasis, 1965)
Semipurified preparations of prothrombin were found to migrate slightly faster than albumin when studied by continuous flow electrophoresis. In contrast, similar studies with plasma, and serum enriched with prothrombin showed substantially slower migration rates for prothrombin. Albumin was shown to be one of the plasma constituents responsible for this change in prothrombin mobility. The broad range of prothrombin mobilities found in plasma is ascribed to multiple interactions between prothrombin and the plasma proteins, and not to the existence of isozymes of prothrombin.